A polymorphism in oocyte pigmentation in natural populations of the glass frog Espadarana prosoblepon (Centrolenidae) - Salazar-Nicholls, María José; Hervas Sotomayor, Francisca; Muñoz-Tobar, Sofía I.; Carrillo, Ana-Belén; Ricaurte, Heisel; Ron, Santiago R.; Romero-Carvajal, Andrés (The international journal of developmental biology, 2021)
The adaptive role of amphibian oocyte melanic pigmentation and its molecular control are still elusive. Here we present evidence of a polymorphism in egg pigmentation in the emerald glass frog Espadarana prosoblepon. In Ecuadorian natural populations of this species, females can lay dark brown or pale eggs that develop into normal pigmented tadpoles and adults. This trait is a sex-limited phenotype which is inherited like a recessive allele that we called pale eggs like (pel). The pel phenotype is exclusive of oocyte cortical melanic pigmentation, which is reduced in comparison to wild type (wt) dark pigmented oocytes. Consequently, pel early embryos are paler in appearance, with reduced melanic pigmentation distributed to early blastomeres and embryonic ectoderm. However, these embryos form normal melanocyte derived pigmentation. Finally, we discuss the origin of this polymorphism and propose the use of E. prosoblepon as a model to study the adaptive role of egg pigmentation.
Gesehen am 20.05.2021